As constituições do ethos especular de estudantes estrangeiros(as) no aprendizado de português como segunda língua dentro de uma perspectiva dialógica de ensino - Souza, Márcia Vanessa dos Santos (2017)
Within a teaching dialogic perspective, practices of Portuguese‟s teaching as a second language (PL2) and discursive constructions of the emerging specular ethos were analyzed in this context. From these considerations, this work aims to consider on the specular ethos (SOUTO MAIOR, 2009) of foreign students in a dialogic context (BAKHTIN, 2014) of Portuguese‟s teaching and learning as a second language (PL2). In this sense, it was asked: How are the practices of teaching dialogic perspective in the context of PL2 developed? Which specular ethos was built within this teaching dialogic practice of PL2? Which proposals of actions for the teaching of PL2 can be developed from observing the construction of the specular ethos? This research predicted the work with the language as social construction (BAKHTIN, 2014; MOITA LOPES, 2002; MAINGUENEAU, 2008), since it departed not only from the inscriptions of the subject as the author of his speech, but mainly of his relationship with the other, which, in the case, presented cultural differences (WOODWARD, 2014) due to the context in which he was inserted. This research has a qualitative character of ethnographic nature (ANDRÉ, 1989; 1995) since it aims to understand the meanings and socio-cultural values presented in the collectivity, within the interpretative perspective of Applied Linguistics (MOITA LPES, 2006). The construction of the data occurred in a classroom during an extension course “Textual Production: Portuguese for Foreigners” (FALE/PROEX/UFAL), which was intended to work some discursive genres (BAKHTIN, 2004) in the academic context, a priori, incited by discussions on some social issues in the period from January to March 2016. As a result of the analysis and interpretation of the data, the teaching processing based on a dialogic perspective (BAKHTIN, 2003; 2014), the constitution of specular ethos of PL2‟s student (SOUTO MAIOR, 2009) and proposals of actions for the development of a sensitive teaching, according to the conception of Culturally Sensitive Pedagogy (ERICKSON, 1987; BORTONI-RICARDO, 2001). As a reflection of this teaching perspective, the ethos constituted in this context showed that the meanings of words can be constructed through the encounter with the other, thus stimulating the learning of a second language. In addition, it was observed the importance of the teacher instigate the curiosity and the desire to encounter with the other culture through practices that provide a specular link of the images in the discursive game, so that the students can interact in a second language in a dialogic way.